Minimum Information about a Biosynthetic Gene cluster - Medema, M.; Kottmann, R.; Yilmaz, P.; Cummings, M.; Biggins, J.; Blin, K.; De Bruijn, I.; Chooi, Y.; Claesen, J.; Coates, R.; Cruz-Morales, P.; Duddela, S.; et al. (Nature Publishing Group, 2015)
© 2015 Nature America, Inc. All rights reserved. A wide variety of enzymatic pathways that produce specialized metabolites in bacteria, fungi and plants are known to be encoded in biosynthetic gene clusters. Information about these clusters, pathways and metabolites is currently dispersed throughout the literature, making it difficult to exploit. To facilitate consistent and systematic deposition and retrieval of data on biosynthetic gene clusters, we propose the Minimum Information about a Biosynthetic Gene cluster (MIBiG) data standard.